The oxygen reduction reaction on palladium with low metal loadings: The effects of chlorides on the stability and activity towards hydrogen peroxide - Fortunato, Guilherme V.; Pizzutilo, Enrico; Cardoso, Eduardo S.F.; Lanza, Marcos R.V.; Katsounaros, Ioannis; Freakley, Simon J.; Mayrhofer, Karl; Maia, Gilberto; Ledendecker, Marc (Journal of Catalysis, 2020)
Hydrogen peroxide is considered one of the most important commodity chemicals worldwide but its main production method, the anthraquinone process, poses serious logistical, environmental and safety challenges. Electrocatalytic synthesis through the reduction of molecular oxygen is a promising H2O2 production route. However, the reduction of molecular oxygen is kinetically hindered and stable electrocatalysts with a high activity and selectivity towards the 2-electron transfer reaction are needed. In this work, we evaluated the influence of chloride on catalysts with low palladium loadings on the ORR selectivity towards H2O2. We report the factors and dynamics that influence H2O2 production and highlight synthesis strategies to obtain close to 100% selectivity. By probing the electrode surface after various degradation cycles, we evaluate the role of adsorbing species and the catalysts oxidation states on the hydrogen peroxide selectivity. We systematically modified the catalyst synthesis using different Pd-precursors that were reduced and supported on high surface area graphene nanoribbons. Identical location transmission electron microscopy was used to probe catalyst dynamics during reaction and the activities and selectivities were measured by a rotating ring disk electrode. We probe the potential boundary conditions that lead to catalyst degradation during accelerated stress tests and potentiostatic polarisation and demonstrate how the catalytically active surface can be revived after degradation. The obtained insights can be used as guideline for the development of active, selective and stable catalysts with low noble metal loadings.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Carbon-supported electrocatalyst; Chlorides; Hydrogen peroxide; Oxygen reduction reaction; Palladium; Stability